Torment - Kate, Lauren (New York : Delacorte Press, 2010)
It took Luce and her fallen angel boyfriend, Daniel, an eternity to find one another, but now he has told her he must go away. Just long enough to hunt down the Outcasts, immortals who want to kill Luce. Daniel hides Luce at Shoreline, a school on the rocky California coast with unusually gifted students: Nephilim, the offspring of fallen angels and humans.
Keywords: Angels -- Juvenile fiction; Occult fiction; High schools -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Fantasy fiction; Horror fiction